A Proposed New Appearance of the Iron Stand from Sutton Hoo, Based on Existing Material - Rowan Taylor (EXARC Journal, 2021)
The Iron Stand from Sutton Hoo, Mound 1 was excavated in 1939. While a first tentative interpretation of its original appearance was made in 1952, this was updated in 1972 following a science-led investigation of the artefact. However, some features of the object were not included in the later representation. The examination of these additional features suggests that the basket element of the iron stand may have been welded to the shaft by the lowest ends of its retaining struts, as evidenced by the possible remains of a fireweld in that location. The point A element, currently interpreted as the fallen base of the upper basket, may instead still be in its original position and represent the base of a second, lower basket element. This is evidenced by possible footing corrosion at points A and B, and a localised 45 degree twist in the shaft designed to retain the point A element. Furthermore, evidence suggests that copper-alloy plating was used on the struts of the upper basket element for decorative effect. This plating was also used to retain an iron ring at the lower ends of each strut. These rings were of a sturdier construction than the welded scrolls present at the upper end of the struts and may have served a specific function. Thus the stand may have had a markedly different appearance to that represented since 1972. The cumulative effect of this re-evaluation gives the artefact a more complex appearance than is currently understood.